The world around us Resource pack class 1 - The city school (Lahore ; The City School)
The world around us perforated resource pack for class 1 explores the concept of natural resources and their significance in our daily lives. It introduces young learners to various resources, such as water, air, and plants, emphasizing their importance for survival and the environment. Through engaging activities and visuals, students learn to identify these resources in their surroundings, understand their uses, and recognize the need for conservation. This resource pack aims to instill an appreciation for nature and promote responsible stewardship among young children.
Keywords: Resource packs; General works